Cost Effectiveness of Livestock Guardian Dogs for Predator Control. (6th February 2020) - Saitone, Tina L.; Bruno, Ellen M.
Abstract : Research has shown that livestock guardian dogs (LGDs) are effective at reducing predation by coyotes, but little work has been done to quantify their benefits on sheep operations. We conducted a comprehensive economic assessment that compared benefits and costs of LGDs on the same operation, concluding that LGDs are only cost‐effective for certain types of operations, namely those where LGDs are able to achieve high rates of predator protection efficacy. ABSTRACT: Predation threatens the economic viability of sheep operations in the United States. Many producers recognize the need to complement lethal control methods with nonlethal strategies such as the use of livestock guardian dogs (LGDs), but little information exists on benefits and costs. We report on a comprehensive benefit–cost analysis of the decision to incorporate LGDs onto a sheep operation in Mendocino County, California, USA, based on data collected during 2013–2017, where livestock predation by coyotes ( Canis latrans ) has been a persistent problem. We estimated that for a representative sheep operation with a breeding flock of 500 adult females (ewes), the use of 5 LGDs reduced lambs and ewes lost to coyote predation by 43% and 25%, respectively, for a total savings of US$16, 200 over 7 years. However, we found that costs, which included acquisition and maintenance expenses, exceed benefits of this investment over the 7‐year useful life of LGDs by US$13, 413. Our results inform the adoption of LGDs, demonstrating that LGDs are only cost‐effective for certain types of operations, namely those where LGDs are able to achieve high rates of predator protection efficacy. © 2020 The Wildlife Society.